A Directly Fused Subporphyrin Dimer with a Wavelike Structure. (21st June 2016) - Okuda, Yasuhiro; Tsurumaki, Eiji; Oh, Juwon; Sung, Jooyoung; Kim, Dongho; Osuka, Atsuhiro
Abstract: [Ni(cod)2 ]‐mediated intramolecular reductive coupling of β–β′ linked meso, meso′‐dibromosubporphyrin dimer gave the anti ‐isomer of meso–meso′, β–β′ doubly linked subporphyrin dimer as the first example of a fused subporphyrin dimer. The fused dimer 3 anti displays an wavelike coplanar structure, a perturbed and red‐shifted absorption spectrum, reversible redox behaviors with a decreased electrochemical HOMO–LUMO band gap, and a short S1 ‐state lifetime owing to the delocalized π‐electronic network.